(untitled) (Jurnal Geomine, 2020)
Monthly planning, based on time period, is included in short-term planning. The work phase that plays an important role for effective and efficient mining operations in monthly planning is evaluating the progress of the previous month’s mine and planning the next month’s mining stage. This research was conducted in an open-pit coal mine with the aim of describing a review of mine progress in November 2019 and planning for mining in December 2019. The mining plan includes the determination of the mine boundary, pit progress design, disposal progress, mine hauling road, mining stages, production schedule, and the number of loading hauling and suppor equipment,. Minescape 5.7 software was used in the mine design process and calculation of overburden and coal volumes. The pit limit was determined from the monthly target and the mine design did not exceed the annual design. The number of tools plan takes into account the productivity of available mechanical devices in order to reach monthly targets. The results of the review in November 2019, actual overburden and coal were excavated more than 10% of the target. The pit topography at the end of the month was less than the request level (undercut). Actual horizontal distance and vertical distance in coal getting were according to plan. Whereas in overburden removal, horizontal distance was 11% more than the plan and vertical distance was 7% less than the plan. The planned mine progress in December 2019 uses stripping ratio numbers 3, the area of the bottom pit area is 21.48 Ha with RL -64 and -48, the area of the Low Wall area is 16.72 Ha with RL -16. Coal production in December 2019 is planned to be 400,000 tons, with overburden removal of 1,200,000 bcm. Targets will be achieved with 4 units loading equipment and 96 units hauling equipment for overburden removal and 1 loading equipment and 17 units hauling equipment for coal getting, 3 units dozers in the pit and 2 units dozer at disposal.